Numerical mathematics with GeoGebra in high school - Herceg, Dragoslav; Herceg, Đorđe (Teaching Mathematics and Computer Science, 2008)
We have prepared a suite of motivational examples which illustrate numerical methods for equation solving. Fixed point iteration, Newton's method, secant method and regula falsi method are implemented as GeoGebra tools. Our experience in teaching of numerical mathematics in "Jovan Jovanovic Zmaj" high school in Novi Sad is presented. We have tested pupil proficiency in numerical equation solving with and without use of a computer and the results are presented.